PROYEKSI PDRB ATAS DASAR HARGA BERLAKU MENGGUNAKAN METODE TREND LINIER, PARABOLIK DAN EKSPONENSIAL - Ayub Hanan Yanottama; Wardono Wardono (Universitas Muhammadiyah Semarang, 2017)
GRDP is one of the factor that affect the economic level of a region. This data is often used for various government or private agencies in making a policy. But,GRDP data provider, such as BAPPEDA and BPS publish GRDP data in long oftime. Because of that, author interest to make a projection of Kudus DistricGRDP for year 2017. The purpose of this study is to know the projection orforecasting of Gross Regional Domestic Product (GRDP) of Kudus District in2017 with various methods and trends to find out which trend model mostsuitable for use. The data that used in this article is Kudus Distric's PDRB on thebasis of current price data from 2010 until 2016.Then, GRDP calculated andanalyzed with SPSS 21 program. The conclusion is the GRDP of Kudus Regencycan be projected with linear trend model (Ŷ = 44977759,28 + 6513395,2014 X),parabolic trend model (Ŷ = 46027952,73 + 5813266,236 X + 87516,121 X) and exponential trend model (Ŷ = 48109762,716 e0,093092X). The best model is theparabolic trend model with the projection for 2017 is 98,135,114.4 (in millionrupiah). Keywords: GRDP, projection, forecasting, trend.